Cardiovascular risk and the implications for clinical practice of cardiovascular outcome trials in type 2 diabetes. Issue 3 (June 2020) - Chilton, Robert J.; Dungan, Kathleen M.; Shubrook, Jay H.; Umpierrez, Guillermo E.
Highlights: T2D increases CV risk but good glucose control can help prevent CV complications. CV outcome trials have investigated the CV safety of antihyperglycemic agents. All agents investigated to date have shown CV safety. Certain SGLT-2is and GLP-1RAs have also been shown to reduce CV events. PCPs should take these benefits into consideration for T2D patients with CV risk. Abstract: Cardiovascular disease (CVD) is the primary cause of morbidity and mortality in patients with type 2 diabetes (T2D). This review examines the impact of cardiovascular outcome trials (CVOTs) on clinical practice. To date, all CVOTs have shown non-inferiority versus placebo (both added to standard of care) against a primary endpoint of 3- or 4-point major adverse cardiovascular event (MACE), confirming CV safety of these treatments. Additionally, some CVOTs have shown superiority to placebo against the same MACE endpoint, suggesting a cardioprotective action for these treatments. This is reflected in guideline updates, which primary care physicians should consider when personalizing treatments.